1980
DOI: 10.1207/s15327752jpa4406_4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Regression of Two Types

Abstract: Adaptive regression is considered to be of two types: a relatively uncommunicable private type and a relatively communicable public type. Private adaptive regression was operationalized by hypnotic suggestibility and by a questionnaire. Public adaptive regression was operationalized by two measures of esthetic sensitivity. It was hypothesized that the psychodynamics of the two types are as follows: Hypothesis 1: Private adaptive regression involves engaging in primary process because of secondary process motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In summary, these studies showed creativity to be positively related to both primary process and secondary process shaping of primary process, and the therapeutic process to be positively related to secondary process shaping of primary process, but found other types of adaptive regression to be positively related only to primary process. Predicting the same pattern, Rosegrant (1980) compared aesthetic sensitivity with privately adaptive regression: Aesthetic sensitivity was positively related to secondary process shaping of primary process but not to absolute amount of primary process; privately adaptive regression was positively related to absolute amount of primary process but not to secondary process shaping of primary process.…”
Section: The Communication Dimension Of Adaptive Regressionmentioning
confidence: 99%
“…In summary, these studies showed creativity to be positively related to both primary process and secondary process shaping of primary process, and the therapeutic process to be positively related to secondary process shaping of primary process, but found other types of adaptive regression to be positively related only to primary process. Predicting the same pattern, Rosegrant (1980) compared aesthetic sensitivity with privately adaptive regression: Aesthetic sensitivity was positively related to secondary process shaping of primary process but not to absolute amount of primary process; privately adaptive regression was positively related to absolute amount of primary process but not to secondary process shaping of primary process.…”
Section: The Communication Dimension Of Adaptive Regressionmentioning
confidence: 99%